Reconceptualizing Value-Based Leadership: Its Impact on Integrity and Human Capital Commitment in Islamic Da’wah Organizations - Dida Novandika; Cecep Sastrawijaya (Islam and Social Sciences Review, 2025)
This study aims to develop a Value-Based Leadership model to enhance integrity and human resource commitment within Islamic da’wah organizations. Employing a Systematic Literature Review (SLR) approach within a qualitative-interpretive paradigm, the study analyzes and synthesizes findings from reputable scholarly articles published over the past five years. The analytical process follows structured stages of identification, selection, evaluation, and thematic synthesis of the literature. The findings reveal that Value-Based Leadership exerts a significant influence on integrity through mechanisms of value internalization and leader role modeling. Integrity, in turn, functions as a mediating variable that strengthens the relationship between value-based leadership and organizational commitment. In the context of da’wah institutions, human resource commitment is not solely affective but also encompasses normative and spiritual dimensions, reflecting a more complex construct compared to conventional organizations.This study is limited by the absence of empirical field data; therefore, future research is recommended to empirically test the proposed model using quantitative methods. Practically, the findings offer strategic implications for Islamic da’wah institutions in fostering leadership practices centered on value internalization, integrity reinforcement, and enhanced workforce commitment. Theoretically, this study contributes to the leadership literature by integrating Value-Based Leadership with Islamic values into a comprehensive conceptual framework.